Bushmeat, now on the Web - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A discussion forum on the dangers of eating bushmeat has been started on the Internet (bushmeat@AZA.org)(see Spore 83, p 7). It is drawing attention to the reasons behind the rising consumption of bushmeat in Africa. These include the general...